High mobility 3D Dirac semimetal (Cd₃As₂) for ultrafast photoactive terahertz photonics - Dai, Zijie (2022)
The Dirac semimetal cadmium arsenide (Cd3As2), a 3D electronic analog of graphene, has sparked renewed research interests for its novel topological phases and excellent optoelectronic properties. The gapless nature of its 3D electronic band facilitates strong optical nonlinearity and supports Dirac plasmons that are of particular interest to realize high-performance electronic and photonic devices at terahertz (1 THz = 4.1 meV) frequencies, where the performance of most dynamic materials are limited by the tradeoff between power-efficiency and switching speed. Here, all-optical, low-power, ultrafast broadband modulation of terahertz waves using an ultrathin film (100 nm, λ/3000) of Cd3As2 are experimentally demonstrated through active tailoring of the photoconductivity. The measurements reveal the photosensitive metallic behavior of Cd3As2 with high terahertz electron mobility of 7200 cm2 (Vs)−1. In addition, optical fluence dependent ultrafast charge carrier relaxation (15.5 ps), terahertz mobility, and long momentum scattering time (157 fs) comparable to superconductors that invoke kinetic inductance at terahertz frequencies are demonstrated. These remarkable properties of 3D Dirac topological semimetal envision a new class of power-efficient, high speed, compact, tunable electronic, and photonic devices.